Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Nelayan di Desa Dongkala Kabupaten Buton - Abdul Hadi Bone (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
The coastal and marine areas in Dongkala village are areas that have the potential to provide various benefits to support community survival. This research aims to determine the factors that influence fishermen’s income. The research was carried out in Dongkala village, Buton regency starting from October to November 2023. The research method used quantitative descriptive methods, multiple linear regression analysis models with the help of SPSS v.17.0 software. The sample used was 50 fishermen respondents who were determined using a purposive sampling technique. The results of research partially show that capital, experience, fish prices and education level have a significant effect on fishermen’s income, while simultaneously the variables of fish price, and education level have a significant effect on fishermen’s income in Dongkala village, Buton regency. The policy that needs to be taken from the results of this research is to optimize the ship operational assistance program for fishermen in order to increase the number of catches, the impact of which will provide regional income levels.